2017
DOI: 10.1007/s12094-017-1812-1
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors and the important role of detectable prostate-specific antigen for detection of clinical recurrence and cancer-specific mortality following robot-assisted radical prostatectomy

Abstract: A detectable PSA is affected by factors associated with aggressive prostate cancer. Within men with persistent PSA, those with higher pathologic stage and who received adjuvant ADT are more likely to have CR. Patients with CR, Gleason ≥ 8, and those who received adjuvant ADT must have a close monitoring due to the high rate of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…On the other hand, matching for these risk factors reduced the impact of the post-RP PSA level. An association of adverse clinicopathological parameters with the post-RP PSA level has been reported in several recent studies, in one instance even with the PSA threshold at 0.01 ng/mL [8,[15][16][17].…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, matching for these risk factors reduced the impact of the post-RP PSA level. An association of adverse clinicopathological parameters with the post-RP PSA level has been reported in several recent studies, in one instance even with the PSA threshold at 0.01 ng/mL [8,[15][16][17].…”
Section: Discussionmentioning
confidence: 74%
“…Conversely, persistent levels of PSA (≥0.1 ng/mL) mean that there is a residual biochemically active tumor burden, regardless of imaging findings [ 4 ]. Therefore, persistent PSA is a poor prognostic factor for recurrence after RP [ 4 5 6 7 8 9 10 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…It clearly depends on the study selection/exclusion criteria and the PSA cutoff used. When considering only the largest series and a PSA threshold of 0.1 ng/ml, which is the most used threshold in the available literature, the proportion of patients having a persistently elevated PSA value ranged from 3.1% to 30% [1,2,6,13,14]. For example, in the subgroup of patients undergoing surgery for high-risk and/or locally advanced disease, up to 30% of men after surgery may have persistently elevated PSA values of !0.2 ng/ml (20%, 25%, and 30% in the ROG 9601, SWOG 8794, and ARO 9602 trials, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Immediate ADT has been associated with improved outcomes. Kim et al [11] and García-Barreras et al [13] found that immediate treatment (ADT and/or sRT) improved MFS and CSS in the univariable analysis. Gandaglia et al [23] correlated the use of immediate ADT with improved CSS.…”
Section: Impact Of Salvage Treatmentsmentioning
confidence: 98%
See 1 more Smart Citation